Domandare della forma. Genesi e metodo fenomenologico tra Husserl e il primo Heidegger - Tosca, Federico (Philosophy Kitchen - Rivista di filosofia contemporanea, 2017)
The foundation of the categorial forms is the main aim of the phenomenological effort. From the publication of the Logical Investigations to the last works that have been recollected in Experience and Judgment, it appears that the sensible origin of judgment has always been Husserl’s main concern. Despite the depth of genetic phenomenological themes – i.e. temporal self-constitutive flow, passive syntheses and transcendental logic –, the search for a genesis of higher intellectual forms from real ones fails in taking account of the isomorphism, by preventing itself from obtaining a criterion for the assessment of the origin. The issue of the genesis leads to a critique which focuses on the transcendental reduction. Derrida’s reading of husserlian phenomenology and early Heidegger’s courses on method should, therefore, contribute to hint a reappraisal of the transcendental, which, nevertheless, can be traced in Husserl’s works as well.